2014
DOI: 10.1016/j.ijhydene.2014.09.136
|View full text |Cite
|
Sign up to set email alerts
|

In-situ redox cycling behaviour of Ni–BaZr0.85Y0.15O3−δ cermet anodes for Protonic Ceramic Fuel Cells

Abstract: Abstract:The current work investigates the redox behaviour of peak performing NiBaZr 0.85 Y 0.15 O 3- (Ni-BZY) cermet anodes for protonic ceramic fuel cells (PCFCs) by electrochemical impedance measurements, scanning electron microscopy (SEM) and Xray diffraction (XRD). Peak performing PCFC cermet anodes are documented to require much lower porosity levels than those needed in oxide-ion conducting counterparts. The polarisation behaviour of these optimised PCFC anodes is shown to be drastically impaired by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Strategies to alleviate this problem are to increase the porosity of the anode or to use an uneven distribution of the electrolyte grain size. Nasani et al [413] studied the redox behavior of the anode Ni/BZY cermet and showed a similar expansion of NiO upon reoxidation as the one observed for YSZ/NiO. Their microstructural analysis proved that the microcracks and delamination observed were due to the nickel expansion phase upon reoxidation.…”
Section: Expansion Of Fuel Side Electrodesmentioning
confidence: 73%
“…Strategies to alleviate this problem are to increase the porosity of the anode or to use an uneven distribution of the electrolyte grain size. Nasani et al [413] studied the redox behavior of the anode Ni/BZY cermet and showed a similar expansion of NiO upon reoxidation as the one observed for YSZ/NiO. Their microstructural analysis proved that the microcracks and delamination observed were due to the nickel expansion phase upon reoxidation.…”
Section: Expansion Of Fuel Side Electrodesmentioning
confidence: 73%
“…Accordingly, the corresponding spectra were not analysed using the methods derived for equilibrium or stationary states. In these cases, the intercept of the spectra with the real axis of the Nyquist (Z′, Z″) plot was used to evaluate the resistance [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…YSZ needs high temperature, usually 800–1000 °C, to provide sufficiently high ionic conductivity for practical applications. At such high temperatures, the SOFC needs expensive ceramic interconnects and it is not easy to achieve long-term stability, so several efforts have been made to decrease the operating temperature of SOFCs. Proton-conducting oxides potentially have higher ionic conductivity relative to oxide-conducting membranes at intermediate or low temperature because of the proton’s smaller size and lower transport activation energy. Hydrogen-fed protonic ceramic membrane fuel cells with a Ni anode have been intensively studied in recent years. …”
Section: Introductionmentioning
confidence: 99%